The association of serum immunoglobulin E levels on outcomes of maximal medical therapy among patients of chronic rhinosinusitis - Majumder, Riashat Azim; Rahman, Mohammad Habibur; Naha, Abirvab; Mamun, Abdullah Al; Sayied, Jaber Al; Rahman, Sheikh Hasanur (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Chronis rhinosinusitis (CRS) is one of the highest prevalent diseases affecting a large population with significant impact on quality of life (QoL) and health care burden. It is almost universally accepted that before surgical therapy is considered, maximal medical therapy (MMT) should be used.Serum immunoglobulin E (IgE) level is a valuable diagnostic parameter in the severity of CRS patients. If relationship between outcomes of medical therapy with different levels of pretreatment Ig E levels can be established, then it may be use as a predictive factor to prioritize between medical treatment or surgery among CRS patients. Objectives: This study aims to see whether the pretreatment serum immunoglobulin E (IgE)levels of patientswith Chronic rhinosinusitis (CRS) have any association on the outcomes of maximal medical therapy (MMT). Methods: This quasi-experimental study wasconducted in the Department of Otolaryngology-Head & Neck Surgery, BSMMU, Dhaka from March 2017 to July 2019. Seventy cases of CRS were assigned into three groups based on pretreatment IgE level: normal (d”25 IU/ml), moderately raised (>25 to d”149 IU/ml), and high (e”150 IU/ ml). Outcomes were measured by evaluation of changes in Pre- and Post-MMTRhinosinusitis Disability Index (RSDI) and Lund-Mackay (LM) staging of HRCT- PNS. Results: The pre-treatment and post-treatment mean of RSDI and LM scoring indicated a significant difference between normal and moderately raised groups. But High IgE showed no significant statistical differences between pretreatment and post treatment mean RSDI and LM scoring. Conclusion: Patients of chronic rhinosinusitis withnormal and moderately raised pretreatment serum IgE levels were significantly responded to maximal medical therapy. Whereas patients with high level of IgE had poorimprovement with maximal medical therapy. Bangladesh J Otorhinolaryngology 2023; 29(2): 81-88